Emerging role of whole-body 18F-fluorodeoxyglucose positron emission tomography as a marker of disease activity in patients with sarcoidosis: a systematic review - Treglia, G.; Taralli, S.; Giordano, A. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2011)
Objective: This study was designed to systematically review the emerging role of whole-body positron emission tomography (PET) with 18F-Fluorodeoxyglucose (FDG) in patients with sarcoidosis. Design: A comprehensive literature search of published studies through December 2010 in PubMed/MEDLINE and Embase databases regarding whole-body FDG-PET and PET/CT in patients with sarcoidosis was performed. Results: Ultimately, we identified nine studies comprising a total of 379 patients with sarcoidosis. Main findings of the included studies are presented. Conclusions: from this systematic review we can summarize that: 1) positive FDG-PET findings should be interpreted with caution in differentiating sarcoidosis from other inflammatory diseases and malignant abnormalities; 2) FDG-PET seems to be a very useful molecular imaging method in assessing disease activity, in staging and identifying occult sites, and in monitoring treatment response in patients with sarcoidosis; 3) FDG-PET shows a better diagnostic accuracy compared to 67Ga scintigraphy in patients with sarcoidosis, because of a better sensitivity of FDG-PET (mainly due to the high quality of FDG-PET images with superior contrast and spatial resolution compared to 67Ga scintigraphy) in addition to several practical advantages (less radiation exposure, shorter time between injection and imaging).